2016
DOI: 10.1111/fare.12187
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Ordering of Supportive Dyadic Coping, Commitment, and Willingness to Sacrifice

Abstract: Drawing from interdependence theory and focal participants (anchors) and their intimate partners who remained coupled at Waves 1, 3, and 5 of the German Family Panel (pairfam; N = 1,543), the authors examined the temporal ordering between anchor and partner supportive dyadic coping with anchor commitment and willingness to sacrifice for an intimate partner. Autoregressive cross‐lagged modeling analyses revealed that anchor and partner supportive dyadic coping predicted higher levels of commitment and willingne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
(52 reference statements)
4
19
0
1
Order By: Relevance
“…As a result, 3,743 of the anchors' partners joined pairfam and provided annual survey data. M. D. Johnson and Horne () compared demographic variables for anchors whose partners participated in pairfam ( n = 3,743) versus those whose partners did not participate ( n = 3,491) and found that those with participating partners tended to be older, were in longer term relationships, had more children, and reported a higher household income than those whose partners were not in the study. We also examined our focal variables of interest in this study among those with and without a participating partner and found anchors whose partner joined the study were slightly less willing to sacrifice, t (6917.74) = −2.178, p = .029, d = −.05, than those without a partner in the study and found no differences in unmitigated communion, t (6914.12) = −.570, p = .569, d = −.01.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, 3,743 of the anchors' partners joined pairfam and provided annual survey data. M. D. Johnson and Horne () compared demographic variables for anchors whose partners participated in pairfam ( n = 3,743) versus those whose partners did not participate ( n = 3,491) and found that those with participating partners tended to be older, were in longer term relationships, had more children, and reported a higher household income than those whose partners were not in the study. We also examined our focal variables of interest in this study among those with and without a participating partner and found anchors whose partner joined the study were slightly less willing to sacrifice, t (6917.74) = −2.178, p = .029, d = −.05, than those without a partner in the study and found no differences in unmitigated communion, t (6914.12) = −.570, p = .569, d = −.01.…”
Section: Methodsmentioning
confidence: 99%
“…We could locate no research examining the long‐term development of these variables. The longitudinal work in this area has examined the interrelation of sacrifice with relational and individual constructs using daily diary (Helgeson et al, ; Impett et al, ; Ruppel & Curran, ) and panel data (M. D. Johnson & Horne, ) or has examined consequences of unmitigated communion and sacrifice on future personal and relational well‐being (Aubé, ; Impett et al, , ; Stanley, Whitton, et al, 2006; Van Lange et al, ). The data contain four biennial assessments of willingness to sacrifice and unmitigated communion from a large, diverse sample of partnered individuals, making them ideally suited for examining the longer term development of each construct.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of sacrifice in relationships has been assessed in several ways, including satisfaction with sacrifice (Stanley, Whitton, Sadberry, Clements, & Markman 2006), a willingness to sacrifice (Van Lange et al, 1997), or frequency and variety of sacrificial acts themselves, which can be measured via self-report (e.g., Totenhagen, Curran, Serido, & Butler, 2013) or behavioral observation (e.g., Van Lange et al, 1997). Sacrifice is also often considered a salient component of commitment (Stanley & Markman, 1992), given that the two constructs are closely intertwined (e.g., Johnson & Horne, 2016), yet conceptually distinct (e.g., Monk, Vennum, Ogolsky, & Fincham, 2016). Sacrifice has also been linked with other pro-relationship processes, such as dyadic coping (Johnson & Horne, 2016), accommodation and investment (e.g., Etcheverry & Le, 2005), attachment (e.g., Etcheverry et al, 2013;Impett & Gordon, 2010;Ruppel & Curran, 2012), and relationship quality (i.e., satisfaction, enjoyment, conflict, closeness; Impett et al, 2005).…”
Section: Interactive Threat-mitigation Maintenance Processesmentioning
confidence: 99%
“…Sacrifice is also often considered a salient component of commitment (Stanley & Markman, 1992), given that the two constructs are closely intertwined (e.g., Johnson & Horne, 2016), yet conceptually distinct (e.g., Monk, Vennum, Ogolsky, & Fincham, 2016). Sacrifice has also been linked with other pro-relationship processes, such as dyadic coping (Johnson & Horne, 2016), accommodation and investment (e.g., Etcheverry & Le, 2005), attachment (e.g., Etcheverry et al, 2013;Impett & Gordon, 2010;Ruppel & Curran, 2012), and relationship quality (i.e., satisfaction, enjoyment, conflict, closeness; Impett et al, 2005). Although sacrifices are often considered good for relationships, they may become maladaptive if they are made by only one partner who underbenefits as a result of this inequality.…”
Section: Interactive Threat-mitigation Maintenance Processesmentioning
confidence: 99%
“…Firstly, attitude and other specific perspectives of the process of sacrifice were chosen to explain the different associations. For example, higher sacrifice willingness is related to stronger commitment, greater relationship satisfaction and stability (Johnson and Horne, ; Powell and Van Vugt, ; Van Lange, P.A., ; Van Lange, S. M., 1997); while sacrifice cost, such as holding back and suppressing negative emotions during sacrifice, may result in a decrease in emotional wellbeing and relationship satisfaction and stability (Impett et al ., ; Impett, Le, et al ., 2014; Le and Impett, ; Righetti, Balliet, Visserman and Hofmann, ; Whitton et al ., ). Secondly, some related theories were applied to the study of sacrifice to explain the paradox.…”
Section: Introductionmentioning
confidence: 99%